Smash his camera [videorecording (DVD)] - Gast, Leon; Galella, Ron (Distributed by Magnolia Home Entertainment, 2010)
Ron Galella, notorious paparazzo, captured some of the most memorable celebrity photographs. In order to do so, he suffered everything from a restraining order to a broken jaw. Includes archival footage of Grace Kelly, Clark Gable, Brad Pitt, Marlon Brando, and more.